2019
DOI: 10.21203/rs.2.18004/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The extent of Knowledge and practice toward neonatal resuscitation among nurses and midwives in public hospitals of South Wollo, northeast Ethiopia: Cross-sectional study

Abstract: Background: The neonatal period is the most vulnerable time for child morbidity and mortality. Asphyxia due to poor resuscitation techniques contributed significantly to this vulnerability. Therefore, this study is aimed to assess the extent of knowledge and practice towards neonatal resuscitation among nurses and midwives in public hospitals of south Wollo northeast Ethiopia. Method: Institutional based cross-sectional study design was employed among 143 study participants selected by a simple random sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…Salary, academic qualification, year of experience in work, recent performance in work, and confidence in offering HBB were not significantly associated with the skills of health professionals on HBB. This is in line with the studies done in Ghana, Afghanistan, and Northwest and Northeast Ethiopia [24, 31, 42, 43]. But, incongruent with the study conducted in Eastern Ethiopia [32].…”
Section: Discussionsupporting
confidence: 86%
“…Salary, academic qualification, year of experience in work, recent performance in work, and confidence in offering HBB were not significantly associated with the skills of health professionals on HBB. This is in line with the studies done in Ghana, Afghanistan, and Northwest and Northeast Ethiopia [24, 31, 42, 43]. But, incongruent with the study conducted in Eastern Ethiopia [32].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, midwives exhibited a suboptimal mean knowledge score (60.9%). This nding was in parallel with a study done in Afghanistan (66% mean score) (23), Ghana( mean score of 61.8%) (13), and South wollo,Ethiopia (66.8% mean score) (30). However, our result surpassed that of a study conducted in North West Ethiopia, where the mean knowledge score was 42.8%.…”
Section: Discussionsupporting
confidence: 89%
“…and South Wollo, Ethiopia (64.5%) (30)(31)(32). However, the nurses' knowledge score was higher than that reported in a study from the Gondar Teaching Hospital, Ethiopia (43.9%) (19), and another study conducted in a selected public hospital in Addis Ababa, Ethiopia (46%) (25).…”
Section: Discussionmentioning
confidence: 99%
“…The nding from this study indicated that the good knowledge level of the participants was 58.2%, in this study the participants had greater knowledge scores than the study conducted in south Wollo among health care professionals with their good knowledge score of 32.9% 19 . Their mean score of knowledge was 73.77% and which was higher than an experimental study done on nursing students and their mean score was 63.33%, another cross sectional study done on health professionals working in selected hospitals in south Wollo Ethiopia with their mean score is 68.56% 19,20 . The difference might be due to study period, and participants in this study were recent to take their course and most of them are in attachment time in the pediatrics unit.…”
Section: Factors Associated With Participants Attitude Towards Nrmentioning
confidence: 43%